2017
DOI: 10.1002/adom.201700941
|View full text |Cite
|
Sign up to set email alerts
|

Implantable and Biodegradable Poly(l‐lactic acid) Fibers for Optical Neural Interfaces

Abstract: represent inferior compatibility with biological systems (especially soft brain tissues) due to their high stiffness and long-time stability, which lead to deleterious effects like tissue damage, inflammation, and rejection. [4] Flexible and stretchable polymeric fibers with designed microstructures are explored for neurological studies, enabling integrated electrical sensing, optical stimulation, and controlled microfluidic delivery. [5] In medical practice, biodegradable organic and inorganic materials incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
150
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(151 citation statements)
references
References 44 publications
0
150
1
Order By: Relevance
“…In 2018, Fu et al reported PLLA optical fibers to be used as a bioresorbable optical neural interconnection between biological matter and optical instrumentation, thanks to negligible optical losses and high transmission coefficient (about 95%) of amorphous PLLA in the visible range . The fiber diameter was tuned to about 220 µm, like that of standard silica optical fibers, to facilitate interconnection with commercial optical components.…”
Section: Bioresorbable Optical Devicesmentioning
confidence: 99%
“…In 2018, Fu et al reported PLLA optical fibers to be used as a bioresorbable optical neural interconnection between biological matter and optical instrumentation, thanks to negligible optical losses and high transmission coefficient (about 95%) of amorphous PLLA in the visible range . The fiber diameter was tuned to about 220 µm, like that of standard silica optical fibers, to facilitate interconnection with commercial optical components.…”
Section: Bioresorbable Optical Devicesmentioning
confidence: 99%
“…Under these circumstances, biointegrated electronic and optical devices that dissolve naturally in physiological conditions have received much attention since potential risk of surgical complications can be avoided. Comprising solely of biodegradable active materials (metals, semiconductors, and dielectrics) and encapsulants, implantable optoelectronic devices consisted of photonic crystals, photodetectors, solar cells, waveguides, and light emitters can dissolve in biological environments in a controlled manner after use (Figure f).…”
Section: Materials Devices and Systemsmentioning
confidence: 99%
“…One of the established tools for intracranial light delivery and detection is by use of implantable optical fibers (and waveguides in most cases) for deep brain optogenetic stimulation and fluorescence detection in vivo . As to the optical neural interface, standard silica glass, fibers, and waveguides based on flexible, stretchable and even biodegradable materials have been thoroughly explored . Recently, developed multifunctional fibers incorporate electrodes and microchannels in the microstructure to enable simultaneous optical stimulation, electrophysiological sensing, and drug delivery …”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Microdrive interfaces have been developed using screws and guide tubes, or via electrically induced thermal expansion . For shorter term implants, biodegradable devices have been proposed to reduce the chronic response, such as flexible optical fibers from poly( l ‐lactic acid) with dimensions similar to standard silica fibers . Intracranial light delivery and detection has been demonstratedin vivo in mice, followed by full degradation …”
Section: Biocompatibilitymentioning
confidence: 99%